The Effect of Using Reading Short Story in Students’ Vocabulary Mastery at SMP HKBP Pajak Baru Belawan - Aritonang, Melly Stevani; Manik, Sondang (English Lecturers and Teachers Association (ELTA), 2021)
This research was aimed to answer the question about the implementation of short story technique whether it can enrich the students’ English vocabulary at Class VIII SMP HKBP PAJAK BARU BELAWAN or not, This is an experimental research. the writer tested the null hypothesis (Ho) which stated that the use of short story cannot enrich the students’ English vocabulary at Class VIII,.The text that used for short story technique in this reseacrh was monologue text (a text that displays story teller) this research focused on narrative text (imaginative experiences) particularly, narrative text was related to the syllabus of the second semester for second grade of junior high school. After the Pretest, Treatment and Post test, there is a significant difference of mean score got both of experimental group (75.25) and the control group (72,75). T-observe > T – table ( P = 0,05) df (38), or 4,46 > 1,686 (P = 0,05). It means that alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected. Thus it can be conclude that by using Reading Short Story affects the students’ vocabulary masterthat there is a significant effect of Reading Short Story in students’ vocabulary mastery. In other words, alternative hypothesis (Ha) is accepted and null hypothesis (Ho) is rejected Keywords: implementation of short story technique,reading short story